Parental Perspectives and Practices in Maintaining the Heritage Language (A Case Study of Preserving Ambonese Malay) - Lekatompessy, Felicia M (Pattimura University, 2021)
Intensity of using national and foreign languages ​​in various sectors indirectly changes people's views on the importance of learning or even maintaining the heritage languages. Consequently, the heritage language may experience a transition because it is rare or even no longer used in daily communication, particularly in the family context. This current study aims to analyze parents’ perspectives about the maintenance of the native language, including their practical ways to preserve the cultural heritage, namely Ambonese Malay. Twenty two parents were randomly selected to participate in this study by filling in the questionnaire that was distributed by electronic system through Google Form. Findings of this research showed that parents have positive language attitudes towards Ambonese Malay and its maintenance as heritage language. Their attitude was revealed in their willingness to teach the Ambonese Malay to their children, use the language in their family communication and at traditional ceremonial and family events, including their expectation of having Ambonese Malay in the school curriculum. Moreover, practical ways of using Ambonese Malay as the dominant language in discussing daily topics at home with the family members were the indications of parents’ persistence ways in preserving the Ambonese Malay in the family domain.